2013
DOI: 10.1208/s12249-013-9977-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Sustained-Release Etoposide-Loaded Poly(ε-Caprolactone) Implants

Abstract: Poly(ε-caprolactone) implants containing etoposide, an important chemotherapeutic agent and topoisomerase II inhibitor, were fabricated by a melt method and characterized in terms of content uniformity, morphology, drug physical state, and sterility. In vitro and in vivo drug release from the implants was also evaluated. The cytotoxic activity of implants against HeLa cells was studied. The short-term tolerance of the implants was investigated after subcutaneous implantation in mice. The original chemical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The morphology of the implant has a significant impact on the drug release rate of drug delivery systems. 28 The SEM images showed that the external and internal surfaces of the MTX-loaded implants were homogenous. These results suggested that the fabrication procedure of the implants yielded a uniform distribution of the drug into the polymeric matrix.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The morphology of the implant has a significant impact on the drug release rate of drug delivery systems. 28 The SEM images showed that the external and internal surfaces of the MTX-loaded implants were homogenous. These results suggested that the fabrication procedure of the implants yielded a uniform distribution of the drug into the polymeric matrix.…”
Section: Discussionmentioning
confidence: 96%
“…The drug release from the implants depends on the environmental conditions, physicochemical properties of the drug and polymers, the shape, size, and drug loading of implants. 28 , 30 The drug release from MTX-loaded implants exhibited an initial burst followed by sustained-release both in vitro and in vivo. The initial burst release may be due to fast dissolution and diffusion of MTX accumulated on the surface of the implants.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal analysis was employed to evaluate the possibility of any physical-chemical interaction between CA and PLGA 50:50 within the polymeric matrix. TG thermogram of CA, PLGA and CAloaded PLGA implants (Figure 3) showed a single well-defined event corresponding to the thermal degradation at temperatures up to 250 °C (Solano et al, 2013). Only the physical mixture showed two events of degradation, the first referring to PLGA and the second related to CA.…”
Section: Thermal Analysismentioning
confidence: 99%
“…The low oral bioavailability of ETP is due mainly to its poor aqueous solubility and membrane permeability. To address these issues, ETP is commercially available as soft gelatin capsules containing ETP incorporated into an emulsion (ETP emulsion) consisting of polyethylene glycol (PEG), glycerol, and citric acid anhydrous (Solano et al., 2013 ). Although the development of ETP emulsion addressed the problems related to ETP solubility, variations in the pharmacokinetic profile persisted (Toffoli et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%